THE RELATIONSHIP BETWEEN INTERPERSONAL COMMUNICATION IN A PSYCHOLOGICAL PERSPECTIVE WITH SELF-HARM BEHAVIOR ON COLLEGE STUDENTS - Dwilanisusantya, Carissa; Arthur, Ifah; Virgie Muhammad, Kemal (Jurnal Ilmiah Publipreneur, 2024)
Self-harm behavior or known as self-harm has become a phenomenon among college students. Self-harm actions carried out by students are caused by the inability to handle the problems faced, more than 70% of respondents stated that self-harm actions were caused by personal problems such as family problems and problems with partners. These self-harm actions cause various impacts, ranging from short-term impacts to long-term impacts which if not supported or handled properly, will disrupt the potential and life of students in the future. This study aims to determine the relationship between interpersonal communication from a psychological perspective with self-harm behavior among college students. This study uses a quantitative approach, with a data collection method using a survey in the form of a questionnaire. The questionnaire was developed by researchers from Schutz's interpersonal needs theory. The results show that interpersonal communication activities from a psychological perspective have a relationship with self-harm actions. Interpersonal communication that meets interpersonal needs in the indicators of inclusion, control, and affection of individuals with self-harm behavior can help change self-harm behavior for the better.